The Influence of Age on the Activity of Selected Biochemical Parameters of the Mouflon (Ovis musimon L.) - Pošiváková, Terézia (Animals (Basel), 2019)
SIMPLE SUMMARY: Blood analyses can be used to assess the health and physiological conditions of wild animals and may provide a precise picture of disease, habitat quality, and other environmental factors. The objective of this study was to analyze the relationship between the age and selected biochemical parameters of the female mouflon (Ovis musimon L.). This study aims to create a possible reference range of biochemical parameter concentrations in the mouflon and to extend the knowledge of this species of wild game within our geographic region. ABSTRACT: Blood analyses can be used to assess the health and physiological conditions of wild animals and may provide a precise picture of disease, habitat quality, and other environmental factors. The objective of this study was to analyze the relationship between the age and the selected biochemical parameters of the female mouflon (Ovis musimon L.). This study creates a possible reference range of biochemical parameter concentrations in mouflon and aims to extend the knowledge of this wild game species within our geographical region. There have not been many studies dealing with this issue in our geographical region. A total of 57 female mouflons aged between 1 and 6 years (1–3 years n = 32, 4–6 years n = 25) and in good physical condition, with an average live weight between 32 and 40 kg were included in the research experiment between the two years. A total of 15 selected biochemical parameters were analyzed. Using statistical analysis, we noticed significant effects of age on almost three-quarters of analyzed biochemical parameters. A statistically significant correlation was observed between age and the parameters of glucose, alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, bilirubin, cholesterol, creatinine, high-density lipoprotein, calcium, triglycerides, and urea. An evaluation of the European mouflon’s biochemical parameters during the whole year may be a reliable method for judging a herd’s condition, diagnosing medical disorders, and preventing the etiology of their occurrence. An analysis of biochemical parameters tells us about the functioning of individual organs as well as the animals’ metabolism. Knowledge of the values of blood parameters is of special importance because they allow us to gather more information on mouflons.